Decoding the Denotative and Connotative Elements in Sony Pictures Animation’s Short Film “Hair Love” (2019) - Lestari, Aulia Nur Fitri (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2023)
The current era has witnessed significant developments in the realms of digital and technology, which have impacted every aspect of our lives, including the art of filmmaking. Not only has technology empowered actors to portray characters, but it has also given rise to animated films to give a message. A prominent scholar, Roland Barthes, proposed that the concept of semiotics could be used as a tool to uncover hidden meanings in various forms of media. The objective of this paper is to examine the denotative elements in Sony Pictures Animation's Hair Love using Roland Barthes' semiotic theory. The purpose of this study is to discuss and explain the nonverbal signs or symbols that appear in the film. The denotative elements present in Hair Love are identified and analyzed using qualitative analysis in this study. The findings of this study reveal the presence of 23 denotative and connotative elements in the movie. Overall, this study contributes to the field of semiotics by analyzing the denotative elements in a contemporary animated film using Barthes' theory. This study's findings can provide useful insights into the use of nonverbal symbols in animated films and how they can be used to convey hidden meanings to the audience. Keywords: Semiotic, Barthes, Connotation, Denotation